Tripodal heptadentate amine ligands with different nitrogen substituents for SARA- and photo-ATRP. (5th May 2022) - Xu, Xiaoling; Wang, Tianheng; Li, Die; Bao, Chunyang; Wang, Yan; Zhang, Jingyu; Peng, Bin; Hong, Mei; Chen, Jing; Zhang, Qiang
Graphical abstract: Highlights: Two tripodal heptadentate amine ligands are modified from Py3 Tren by facile reduction and methylation reactions. Py3 H3 Tren and Py3 Me3 Tren are highly active ligands for ATRP. CuBr2 /Py3 H3 Tren and CuBr2 /Py3 Me3 Tren complexes could mediate SARA ATRP and Photo-ATRP. CuBr2 /Py3 H3 Tren has the fastest reaction rate in Photo-ATRP. Abstract: Tripodal heptadentate amine ligands, tris[ N -(2-pyridylmethyl)-2-aminoethyl]amine (Py3 H3 Tren) and tris[ N -(2-pyridylmethyl)- N -methyl-2-aminoethyl]amine (Py3 Me3 Tren), are used as the active ligands for atom transfer radical polymerization (ATRP). Both of them evolve from a Schiff base ligand, tris[ N -(2-pyridylmethyl)-2-iminoethyl]amine (Py3 Tren), through simple reduction and methylation reactions. Electrospray ionization mass spectrometry is used to investigate the coordination between the ligands and CuBr2 at an equimolar amount in the solution. It reveals that CuBr2 /Py3 H3 Tren and CuBr2 /Py3 Me3 Tren are tripod claw-shaped complexes. Electrochemical studies show that CuBr2 /Py3 H3 Tren has a more negative redox potential and higher reactivity than the other two counterparts. The order of K ATRP of CuBr2 /ligand is Py3 H3 Tren > Py3 Me3 Tren > Py3 Tren. Subsequently, CuBr2 /Py3 H3 Tren and CuBr2 /Py3 Me3 Tren are employed as the catalysts for the supplemental activators and reducing agents (SARA) ATRP of methyl acrylate (MA). Well-defined poly(MA) with controlled molecular weight and low M w / M n could be synthesized with the almost quantitative monomer conversion at room temperature, and CuBr2 /Py3 Me3 Tren has the fastest reaction rate. Photo-induced atom transfer radical polymerization (Photo-ATRP) of MA using Py3 H3 Tren and Py3 Me3 Tren as the ligand are also performed. Photo-ATRP using Py3 H3 Tren has the fastest reaction rate, while the polymerizations using Py3 Me3 Tren has shown lower polydispersity.